Legal Politics of Regulating The Management of Special Economic Zone In Indonesia: A Civil Law Analysis of Obligations and The Implementation of Social Responsibility: Politik Hukum Pengaturan Pengelolaan Kawasan Ekonomi Khusus di Indonesia: Analisis Hukum Perdata terhadap Kewajiban dan Implementasi Tanggung Jawab Sosial - Putra, Bayu Mogana (Lex Renaissance, 2025)
Social responsibility is a moral and legal obligation that must be fulfilled by business entities in supporting sustainable economic development. In the context of Special Economic Zone in Indonesia, the implementation of social responsibility holds particular urgency as Special Economic Zone serve as strategic instruments of the state in promoting investment, exports, and national economic growth. However, to date, the regulation concerning the obligation and implementation of social responsibility within Special Economic Zone remains abstract and lacks a comprehensive integration within the national legal politics framework. This study aims to analyze the legal politics of Special Economic Zone regulation in Indonesia in relation to the implementation of social responsibility, and to explore the importance of such regulation from a private law perspective. This research is normative in nature, employing a statutory approach and a conceptual approach. The legal materials used consist of primary sources such as Law Number 39 of 2009 concerning Special Economic Zone and its derivative regulations, along with secondary legal materials including literature and scholarly studies. Data analysis is conducted systematically by constructing an ideal legal framework. The results indicate that the regulation of social responsibility in Special Economic Zone lacks a solid philosophical, juridical, and sociological foundation. Therefore, legal policy reform is urgently needed, both through legislative updates and the establishment of detailed technical regulations, to ensure legal certainty and support social sustainability in the development of Special Economic Zone in Indonesia.